2012
DOI: 10.1007/s13205-012-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term storage of alginate-encapsulated protocorm-like bodies of Dendrobium nobile Lindl.: an endangered medicinal orchid from North-east India

Abstract: Synthetic seed technology is an exciting and rapidly growing area of research as deals with conservation and storage of rare, endangered and desirable genotypes along with its easy handling and transportation. As propagation of many ornamental and medicinally important plant species is labour intensive, application of different growth retardants and osmotica in simple artificial seed system would dramatically reduce labour requirement by storing the germplasm in vitro. Moreover, the primary aim of developing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However, Saiprasad and Polisetty (2003) observed complexation of 3% sodium alginate with 75 mM CaCl 2 for 20-30 min as optimum combination for proper hardening of beads in different orchids. Also Mohanty et al (2013) found 3% sodium alginate solution with 10 mM CaCl 2 as favourable proper synthetic seed formation in Dendrobium orchids. The increased in sodium alginate concentration at 3% along with gradual raised in CaCl 2 at 25, 50, 75 and 100 mM produced soft, firm and very less transparent beads which were not suitable for encapsulating plant propagules.…”
Section: ------------------------------------------------------------mentioning
confidence: 87%
“…However, Saiprasad and Polisetty (2003) observed complexation of 3% sodium alginate with 75 mM CaCl 2 for 20-30 min as optimum combination for proper hardening of beads in different orchids. Also Mohanty et al (2013) found 3% sodium alginate solution with 10 mM CaCl 2 as favourable proper synthetic seed formation in Dendrobium orchids. The increased in sodium alginate concentration at 3% along with gradual raised in CaCl 2 at 25, 50, 75 and 100 mM produced soft, firm and very less transparent beads which were not suitable for encapsulating plant propagules.…”
Section: ------------------------------------------------------------mentioning
confidence: 87%
“…However, no regeneration was recorded from encapsulated nodal buds stored for 60 days at 23 ± 2°C (Table 2). There are reports on rupture of encapsulation matrix during storage that hindered further storage 25,27 . However, in the present study rupture of encapsulation matrix was not observed; instead the nodal buds turned yellowish or brownish with increase in storage duration resulting a decline in regeneration (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover genetic diversity studies indicate that D. nobile from Northeast India has a comparatively higher rate of genetic diversity [6,7]. The orchid, being prized for its immense commercial importance, is often subjected to unrestrained anthropogenic pressures, thereby threatening its natural population [8]. In addition to its health benefits and economic value, D. nobile is also a wonderful source of experimental material to expound gene expression and regulation because of its versatile characteristics; the availability of decent numbers of expressed sequence tags of this species also augmented this study.…”
Section: Introductionmentioning
confidence: 99%